Remote detection of Artemia slicks using multisatellite observations: spectral, spatial and temporal considerations - Xin Wang; Jingyi Tian; Li Ma; Xianghan Sun; Liqiao Tian (International Journal of Digital Earth, 2024)
ABSTRACTArtemia has high commercial and ecological value, but few studies have considered the spectral, spatial and temporal requirements of Artemia multisatellite observations. Adopting Landsat-8 OLI and Sentinel-2 MSI as examples, we mainly analyzed and compared their Artemia slick detection performance considering spectral sensitivity, spatial resolution and revisit cycle. First, the NIR bands of both sensors were most sensitive in Artemia slick detection. Second, compared to that of 2 m GF-6 PMS fusion images, the spatial uncertainty of MSI images was approximately ±16% using the brine shrimp index (BSI) to extract Artemia slicks, better than that of OLI images. The OLI and MSI detection limits under ideal conditions were 0.77% and 1.69%, corresponding to the smallest detectable Artemia slick sizes of approximately 6.93 and 1.69 m2. Third, multisatellite observations could improve dynamic Artemia slick monitoring ability. The OLI and MSI combination could enhance the monthly average observation frequency to 6.58 times. Finally, we examined the influences of the selected near-infrared (or red-edge) bands and Artemia slick width on the extraction results and analyzed detection limit changes and sensor consistency through practical considerations. Overall, these findings could provide support for remote Artemia observation, aiding in fishery management, global mapping and biomass estimation.